Badania marketingowe na rynkach wzrostowych i dojrzałych - Marciniak, Beata (Marketing Research on Growing and Mature Markets, 2006)
In the paper the specificity of growing and mature markets is described. The author also analyzes in which way the different objectives of companies operating on the growing and mature markets imply the scope of information needs, as well as the scope of useful types of marketing research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 362-368